Modulation of mRNA 3′-End Processing and Transcription Termination in Virus-Infected Cells - Vijayakumar, Aarthi; Park, Annsea; Steitz, Joan A. (Frontiers in Immunology, 2022)
Eukaryotic mRNA 3´-end processing is a multi-step process beginning with pre-mRNA transcript cleavage followed by poly(A) tail addition. Closely coupled to transcription termination, 3´-end processing is a critical step in the regulation of gene expression, and disruption of 3´-end processing is known to affect mature mRNA levels. Various viral proteins interfere with the 3´-end processing machinery, causing read-through transcription and altered levels of mature transcripts through inhibition of cleavage and polyadenylation. Thus, disruption of 3´-end processing contributes to widespread host shutoff, including suppression of the antiviral response. Additionally, observed features of read-through transcripts such as decreased polyadenylation, nuclear retention, and decreased translation suggest that viruses may utilize these mechanisms to modulate host protein production and dominate cellular machinery. The degree to which the effects of read-through transcript production are harnessed by viruses and host cells remains unclear, but existing research highlights the importance of host 3´-end processing modulation during viral infection.